DNA-based mutation analysis of Bruton's tyrosine kinase gene in patients with X-linked agammaglobulinaemia. - Vorechovský, I; Vihinen, M; de Saint Basile, G; Honsová, S; Hammarström, L; Müller, S; Nilsson, L; Fischer, A; Smith, C (1995)
The identification of the BTK (Bruton's tyrosine kinase) gene defective in human immunoglobulin deficiency X-linked agammaglobulinaemia (XLA) and characterisation of BTK exon-intron boundaries has now allowed the analysis of mutations and polymorphisms at the level of genomic DNA. Using Southern blot analysis and the polymerase chain reaction single strand conformation polymorphism (PCR-SSCP) assay, amplifying all 19 exons and the putative promoter region with a single annealling temperature, mutations have been identified in 19 out of 24 unrelated patients diagnosed as having XLA. Apart from a large deletion involving exon 19, nine missense (F25S, R288W, 1370M, M509V, R525P, N526K, R562W, A582V and G594R), two nonsense (E277X and R525X), five frameshift and two splice site mutations have been found affecting most coding exons and all major enzyme domains. No mutations or polymorphisms were detected in the putative promoter region. A single nucleotide deletion located in the last exon, resulting in a truncation of the eight C-terminal residues of Btk and a typical XLA phenotype, indicates structural and/or functional importance of Btk helix I in the catalytic domain. Although allelic heterogeneity at the BTK locus may partly explain clinical variability in families with XLA, compensatory and redundant mechanisms involved in B-cell development must play a role in the phenotypic diversity of the disease.